Reshaping the future: a survey on nationalist literature in Malaysia - Abdul Manaf, Nor Faridah; Hashim, Ruzy Suliza (Dewan Bahasa dan Pustaka, 2001)
The article looks at a few samples of nationalist writings from 1980s-1990s